The Causality Of Liquidity And Profitability In Indonesian Banking - Chajar Matari Fath Mala; Sapto Jumono; Windarko Windarko; Yusuf Iskandar (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This research examines the causality between liquidity levels and profitability in Indonesia's banking sector. The study will examine bank profitability and external liquidity from 2012 to 2022, using Net Interest Margin (NIM) and Loan-to-Deposit Ratio (LDR). The econometric analysis of panel data will involve using VAR/VECM techniques. The study discovered that an increase in LDR positively impacts NIM, indicating the bank's ability to maintain liquidity flexibility in the short and long term. However, short-term LDR has a negative impact on NIM. The relationship between NIM and LDR is reciprocal, as the Variance Decomposition Model reveals that NIM has a greater impact on its fluctuations than LDR. On the other hand, LDR has a significantly greater impact compared to NIM. Monetary policymakers should consider NIM and LDR because they impact the bank's long-term strategic planning. Furthermore, there is a need for additional training on NIM and LDR analysis among workers.